Care Quality for Adult Medicaid Beneficiaries With Type 2 Diabetes Varies by Primary Care Provider Subspecialty - Robert Mayberry; Rita Finley; Ernest Alema-Mensah; Trobiand Davis (Georgia Southern University, 2006)
The Georgia Medicaid primary care case management (PCCM) program, phased in over the 1994-1997 period, has now given way to a capitated managed care model of regional care management organizations (CMOs). Using Georgia Medicaid eligibility and provider claim data for 1996-1998, this study investigated diabetes care quality and whether it varied by primary care provider subspecialty in a longitudinal follow-up of newly diagnosed adults with type 2 diabetes during the early phase of the PCCM program. Results indicated that the quality of diabetes care was suboptimal and varied significantly by PCP subspecialty, with patients seen by generalists least likely to have their HbA1c monitored as recommended during office visits (odds ratio = 0.34, (95% confidence interval 0.16-0.73). No PCP subspecialty consistently performed better or worse on all diabetes care quality indicators investigated. The lessons learned from this investigation are that variations in Medicaid care quality by PCP subspecialty is likely to remain and the new CMO model of care will unlikely demonstrate immediate improvement in diabetes care quality.